Remitansi dan Pemanfaatannya : (Studi pada Pekerja Perempuan Indonesia di Pabrik Pulau Penang Malaysia) - Hidayatun Nupus (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Migrant workers or often known as Indonesian workers are workers who are facilitated to find work abroad and of course facilitated by the government. The purpose of this study is to determine the factors that influence the amount of remittances, determine the workload obtained, and determine the correlation between the level of workload and the amount of remittances and the utilization of remittances. This research uses observation, in-depth interviews, and documentation methods in the data collection process. The theory used in this research is Rational Choice from James. S. Coleman. The technique of determining informants using purposive with the criteria of factory workers who live in Jambul View apartments. The results showed that there are several factors that influence the amount of remittances, namely family dependents, daily needs of migrant workers, and workload. In addition, the utilization of remittances is used to meet family needs, pay debts, pay for siblings education, and to save.